Características da capacidade de inovação orientada para a inovação frugal através de estudos de caso - Maleski, Stefano (2023)
This Thesis, in a traditional monolithic format, analyzes, on the one hand, Frugal Innovation, which describes a phenomenon whereby solutions are developed to serve customers who demand more accessible products, in addition to helping to solve social and environmental problems, on the other hand, the Capacity of Innovation that represents the adaptability and change of resources and capabilities, responding to external stimuli. By characterizing both concepts, in addition to the concept of Organizational Innovation, the latter being the background for the study. Propositions were formulated aiming to integrate all the concepts and then, based on the literature and propositions, three case studies were made in companies that have proven to innovate mainly in a frugal way in the last years and thus characterize within the theories what is applied in practice, forming the Capacity of Frugal Innovation, a model that can be applied to companies that seek to be able to innovate in this way, in addition to bringing a new path to be further explored by the academy, this is the beginning of a path with diverse possibilities and applications that highlighted the importance features such as culture, strategy, innovation capabilities and how they should be applied. The importance of this thesis is due to the fact that structured innovation no longer explains the phenomenon that has been occurring in several countries, especially in the post-pandemic period in which the world found itself in supply shortages, logistical costs and products rising, making even its mitigation is more urgent, which is the Frugal Innovation Capacity.